COVID 19: Without distinction of race, sex or socioeconomic position; No one is safe. - Tello-Majluf, D. (2020)
I have read with great pleasure and gratitude the article Protecting Health Personnel in the COVID- 19 Pandemic By Jhony De La Cruz, publish March, 21, 2020 in this prestigious journal. In response to this very informative article on the COVID-19 pandemic, I would like to express my sadness and share my experience of what we are living first hand here in the epicenter of the United States, New York city but first let me begin by giving you an idea of the timeline that has taken place to get us where we are today. As we all know, there was a whistleblower doctor in Wuhan, China, his name was Li Wenliang, he was an ophthalmologist. On December 31 st 2019,  China confirmed the existence of the new virus initially called 2019-nCoV now referred to as SARS-CoV2, but Dr. Li Wenliang said he had observed many of his colleagues get very ill, fall sick, and observed 4 die from the virus in the 2 months prior to that.